Gender-neutral vs. gender-specific strategies in school-based HPV vaccination programs: a systematic review and meta-analysis - Chandeying, Nutthaporn; Khantee, Puttichart; Puetpaiboon, Sirada; Thongseiratch, Therdpong (Frontiers in Public Health, 2025)
IntroductionThis systematic review and meta-analysis evaluated whether gender-neutral (GN) or gender-specific (GS) strategies more effectively enhanced knowledge, intention, and uptake of HPV vaccination among students in educational settings.MethodsA comprehensive literature search of PubMed, Scopus, Web of Science, and Cochrane Library identified 17 randomized controlled trials encompassing 22,435 participants (14,665 females, 7,770 males). Random-effects models were used to calculate standardized mean differences (SMDs) for knowledge and intention, and risk differences for vaccination uptake.ResultsGN strategies achieved higher improvements in knowledge (SMD = 0.95) and intention (SMD = 0.59) compared with GS (SMD = 0.68 for knowledge, SMD = 0.14 for intention), and displayed a greater increase in uptake (5.7% versus 2.5% in GS), although this uptake difference was not statistically significant. Heterogeneity was more pronounced for knowledge outcomes and moderate for GS uptake results.DiscussionDespite GN approaches seemingly offering more robust enhancements in HPV-related knowledge and vaccination intention, additional research with robust designs and longer follow-up is required to determine whether GN interventions definitively outperform GS strategies in achieving statistically significant increases in actual vaccination uptake.